Impact of Affirmative Action and Boychild Socio-Economic Development in Zombo District: A Case Study of Paidha Sub County - Daphine Kacwinyrwoth (Uganda Christian University, 2024)
This study aimed to examine affirmative action's impact on boys' socioeconomic development in Paidha Sub-County, Zombo District, located in the West Nile region of Uganda. The study's specific objectives were to determine the level of affirmative action for boys in Paidha Sub-County, assess the socioeconomic development of boys in the same area, and evaluate the impact of affirmative action on the socioeconomic development of boys in Paidha Sub-County. This study was prepared with both quantitative and qualitative data analysis and used purposive and simple random sampling techniques. The sample population was 60 out of 86 and the target population comprised of boy children in households, community workers, community leaders, health workers, NGO representatives, and government officials. 60 questionnaires were produced and distributed to the target group however, 56(93%) questioners were returned and only 4 were not returned (07%). The data analysis was based on three objectives drawing the researcher to the conclusion that affirmative, Action should be reviewed and provide inclusivity of both genders, furthermore, people need thorough sensitization to understand certain concepts. The researcher recommends collaboration with the government, social workers, stakeholders, and the community to understand the actual problems the child is experiencing due to the current affirmative actions to improve their socioeconomic development.
Undergraduate Research